The Role of Data Governance and Ethical AI in Strengthening Reliability of Healthcare Information Systems - Subekthi, Errysa; Fahreza, Muhammad Rizqi (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
The increasing reliance on digital technologies in healthcare has underscored the importance of robust information systems for ensuring the delivery of high-quality patient care. As healthcare systems adopt artificial intelligence (AI) to support decision-making, the role of data governance and ethical AI has become increasingly vital in maintaining the reliability and trustworthiness of these systems. Data governance involves the frameworks, processes, and standards for managing the quality, integrity, and security of healthcare data, while ethical AI ensures that the algorithms driving healthcare decisions are transparent, fair, and free from biases. This paper explores the crucial role that data governance and ethical AI play in enhancing the reliability of healthcare information systems. It highlights key challenges such as data privacy concerns, algorithmic biases, and accountability, and discusses strategies for improving transparency, data stewardship, and decision-making frameworks. The research further examines the potential impacts of poor data governance and unethical AI practices on patient outcomes, trust in healthcare systems, and overall system efficiency. Through a review of current trends and best practices, this study aims to provide actionable insights for healthcare providers, policymakers, and technology developers in strengthening the integrity and effectiveness of healthcare information systems.